2006
DOI: 10.2214/ajr.05.1440
|View full text |Cite
|
Sign up to set email alerts
|

High-Spatial-Resolution Contrast-Enhanced MR Angiography of Abdominal Arteries with Parallel Acquisition at 3.0 T: Initial Experience in 32 Patients

Abstract: The outlined MR angiography protocol at 3.0 T combined with parallel acquisition technique renders highly reliable and isotropic high-spatial-resolution imaging of the abdominal vasculature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 29 publications
1
16
0
1
Order By: Relevance
“…This finding is in line with a recent report on parallel acquisition MRA at 3.0 T with a sensitivity of 100% and a specificity of 94% compared with digital subtraction angiography in detecting visceral arterial stenosis [31]. In our study, all stenoses depicted on MDCTA were correctly classified on fast MRA by both readers.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is in line with a recent report on parallel acquisition MRA at 3.0 T with a sensitivity of 100% and a specificity of 94% compared with digital subtraction angiography in detecting visceral arterial stenosis [31]. In our study, all stenoses depicted on MDCTA were correctly classified on fast MRA by both readers.…”
Section: Discussionsupporting
confidence: 93%
“…Implementing parallel imaging at 3.0 T provides an additional improvement in image quality of contrast-enhanced MRA of visceral arteries, since at 3.0 T the MRA can be performed with a higher spatial resolution and a faster image acquisition [16,32] and the higher CNR at 3.0 T can be used to further reduce the administered dose of MR contrast agent [32,33]. A recent study has shown better visibility of visceral arteries on MR angiograms acquired on a 3.0-T MR system versus a 1.5-T system in 14 of 15 volunteers [34], and another group obtained reliable high-spatial-resolution images of the abdominal arteries with a parallel acquisition at 3.0 T in 32 patients with excellent sensitivity and specificity values for detection of haemodynamically significant arterial stenosis [31]. However, 3.0-T MRA approaches involve several technical challenges, including the need for a homogeneous radio frequency field that is more demanding to produce at 3.0 T than at 1.5 T, and a four-fold increased specific absorption rate compared to 1.5-T scanners [35].…”
Section: Discussionmentioning
confidence: 99%
“…To counteract the main limitation of parallel acquisition, degradation of SNR [4,5], various strategies can be employed including the use of high magnetic field systems with higher baseline SNR [14,15], and minimizing the noise amplification by using array coils with more channels and improved geometry and sensitivity profile [16,17]. In this study, the outlined peripheral CE-MR angiography protocol showed promising results with high diagnostic image quality for evaluation of arterial-occlusive disease in patients with PVD.…”
Section: Discussionmentioning
confidence: 96%
“…The introduction of 3.0T MR systems into clinical practice, with their higher available signal-to-noise ratio (SNR), has the potential to improve the performance of Gdenhanced fast gradient-echo sequences significantly. The higher SNR gain at 3.0T can be used to reduce acquisition time and improve spatial resolution, and is advantageous when parallel imaging with acceleration factors of 2.0 are considered (19,20). Preliminary results suggest that the SNR can be as much as twice as high as at 1.5T, particularly after contrast administration.…”
Section: Discussionmentioning
confidence: 99%